PREFERENSI KONSUMEN TERHADAP BUAH APEL IMPOR DI TOKO BUAH HOKKY DAN PASAR TRADISIONAL AMPEL SURABAYA - Rahayu, Jeani Noviana; Fauziyah, Elys; Ariyani, Aminah HM (9-772301-994005, 2012)
This study aims to describe the characteristics of consumers who buy imported apples and analyze the attributes of consumer preferences in buying imported apples.  The study was conducted at the Hokky fruit shop  and the Ampel traditional market  in Surabaya. Data analysis was done with descriptive  and conjoint methods. The analysis showed that the attributes that a consumer preference in buying apple imports in order are  the price, color, texture, size and packaging.